2018
DOI: 10.1002/dneu.22630
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Axon Transport in Neuroprotection and Regeneration

Abstract: Retinal ganglion cells and other central nervous system neurons fail to regenerate after injury. Understanding the obstacles to survival and regeneration, and overcoming them, is key to preserving and restoring function. While comparisons in the cellular changes seen in these non-regenerative cells with those that do have intrinsic regenerative ability has yielded many candidate genes for regenerative therapies, complete visual recovery has not yet been achieved. Insights gained from neurodegenerative diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 119 publications
(134 reference statements)
1
6
0
Order By: Relevance
“…7c-d). These phosphorylated forms in the injury experiments may selectively undergo anterograde axonal transport to stimulate MT synthesis and stabilization in regenerating axons [38].…”
Section: Discussionmentioning
confidence: 99%
“…7c-d). These phosphorylated forms in the injury experiments may selectively undergo anterograde axonal transport to stimulate MT synthesis and stabilization in regenerating axons [38].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in non-human primates found that elevations in IOP and reduced OPP were associated with obstruction of axonal transport in the ONH [ 19 , 33 , 52 , 53 , 54 ]. At that time, the IOP rise was mostly acute, and in some cases reaching values above 60 mm Hg or even >100 mm Hg, leading to an expressive decrease in perfusion pressure [ 19 , 33 , 52 , 55 , 56 , 57 ].…”
Section: Axonal Damage In Glaucomamentioning
confidence: 99%
“…In optic neuropathies, the initial injury occurs in the axons of RGCs, and axonopathy precedes death of the soma [25]. In glaucoma, elevated IOP leads to impaired axonal transport, including transport of brain-derived neurotrophic factor (BDNF) [26], which then lead to somatic degeneration [14,27]. In AION animal model, massive axonal degeneration occurs within 7 days after onset [28•], which precedes the first peak of RGC death at day 10 [29].…”
Section: Axonopathy Precedes Rgc Death In Optic Neuropathiesmentioning
confidence: 99%